To the problem of investigating the processes of structure formation in four-component nanoparticles - S.A. Veresov; K.G. Savina; A.D. Veselov; S.V. Serov; A.Yu. Kolosov; V.S. Myasnichenko; N.Yu. Sdobnyakov; D.N. Sokolov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2022)
Various types of configurations of the Au-Cu-Pd-Pt four-component nanosystem, including complex core-shell structures, have been studied. The Monte Carlo method was used as a simulation method, the interatomic interaction was described by the tight-binding potential, i.e. the Gupta potential. According to the results of a series of computer experiments, it was found that four-component nanoparticles of this system do not tend to form a core-shell structure, even though gold atoms have an increased surface segregation. The melting temperatures for the nanosystems under study have been determined. The obtained values are in the range from 1100 K to 1250 K and weakly depend on the composition of nanoparticles (the ratio of the number of atoms). A stoichiometric composition based on these metals was found, for which, during cooling, an FCC crystal structure with inclusions of the HCP phase is formed. However, no distinctive features in the nature of segregation for this stoichiometric composition have been established. All considered stoichiometric compositions in the studied temperature range were stable with respect to decomposition.